2004
DOI: 10.1177/107110070402500805
|View full text |Cite|
|
Sign up to set email alerts
|

Hallux Valgus and First Ray Mobility: A Cadaveric Study

Abstract: After correction of HV deformities with a DSTR and a proximal crescentic osteotomy, first ray mobility in cadaver specimens was significantly reduced. The stabilization of first ray mobility that occurred immediately after surgical correction despite leaving the capsule of the first metatarsocuneiform (MC) joint undisturbed suggests that extrinsic anatomic features may play a role in first ray mobility. Additionally, stability of the first ray may be restored with a bunion procedure that does not sacrifice the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 33 publications
2
47
1
6
Order By: Relevance
“…Joint laxity may be incidental 15,48 or it may be the catalyst that activates other precursor traits. 46,49 -52 Research investigating the mechanisms of deformity should explore the importance of tissue stiffness and joint laxity.…”
Section: Synthesismentioning
confidence: 99%
“…Joint laxity may be incidental 15,48 or it may be the catalyst that activates other precursor traits. 46,49 -52 Research investigating the mechanisms of deformity should explore the importance of tissue stiffness and joint laxity.…”
Section: Synthesismentioning
confidence: 99%
“…The concept of first ray sagittal hypermobility as a primary underlying factor predisposing to hallux valgus was accepted by many authors [31][32][33] who demonstrated a significant decrease of the metatarsocuneiform joint motion after surgery, while others denied the role of hypermobility of this joint in the genesis of hallux valgus [34]. Between these controversial hypotheses we consider that stabilisation of the metatarsocuneiform joint is an important objective in the surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We do not perform Lapidus arthrodesis routinely in revision bunion surgery. Coughlin et al 10 showed that the stability of the first ray may be restored after surgical correction of the hallux valgus deformity despite leaving the capsule of the first tarsometatarsal joint undisturbed. Preoperatively, the need for the Lapidus procedure can be predicted by performing the relocation drawer test.…”
Section: Discussionmentioning
confidence: 99%